Implementation of Data Transmission Using X-10 Protocol within Household Wiring - Tan, Lay Khim (2007)
Home automation refers to applications of technology to control function in the house and communications within the inside and outside world. One of the major benefits of smart homes to consumers is its ability to incorporate energy management features. One smart home system manufacturer claims to be able to reduce the electricity bill by 30% depending on the home consumption. Smart homes can even go further in energy management by keeping track of the energy usage of each and every appliances in the house. Such features allow the user to know what is using too much electricity and adjust things accordingly. It is obvious that if cost is to be minimized, usage of the electricity has to be monitored more accurately and carefully. An automated electrical power meter can be used to achieve this objective. In one version of the automated electrical power meters the power consumption of an appliance can be read remotely by using the existing electrical wiring. In this mode data transmission plays an important role. In this work the transmission of data between the transmitter and the receiver of a house using X-10 protocol is studied and applied. X-10 protocol is a scheme of transmitting signal through existing electrical household cable to control appliances. Therefore, the main objective of this research is to design and assemble the hardware of a transmitter and a receiver for data transmission using power line and to develop the software for a micro-controller.